Imbalance Between Oxidative Stress and Growth Factors in Human High Myopia - Mérida, Salvador; Villar, Vincent M.; Navea, Amparo; Desco, Carmen; Sancho-Tello, María; Peris, Cristina; Bosch-Morell, Francisco (Frontiers in Physiology, 2020)
Myopia is one of the commonest eye pathologies that may affect 2.56 billion people by 2020. Today high myopia is a leading cause of blindness worldwide due to associated ocular illness. Nevertheless, the mechanisms of action and cellular basis for these diseases to develop are unclear in many areas. We conducted a prospective study of oxidative stress and growth factors in human myopic and non myopic eyes in an attempt to understand the underlying physiopathological mechanisms to adequately early diagnose, prevent and treat the retina problem derived from myopia. Aqueous humor samples were obtained from 41 patients being operated for cataracts in our hospital. Axial length, refractive status and complete ophthalmologic examination were recorded. The VEGF and HGF levels were determined by an ELISA kit. Total antioxidant capacity and total nitrites/nitrate levels were established with a lab kit. For the first time, we propose that the direct connection between oxidative damage and different growth factors play a relevant role in myopia after finding statistically significant differences. Likewise, high myopic eyes reflect a misbalance of oxidative stress and growth factors, which may be related to the reduction in blood flux in these eyes.